On the question of definition of the subject area of research in the specialty "Geodesy and land surveying" - Martyn, A.; Trevoho, I.; Ievsiukov, T.; Burshtynska, Kh. (Land Management, Cadastre and Land Monitoring, 2021)
The article discusses the content of the subject area of research introduced in 2015 in Ukraine specialty "Geodesy and Land Management" as a set of all subjects, the properties of which and the relationship between which should be considered in the relevant scientific theory. Based on the established practice of research work, as well as international approaches to determining the subject of modern geodesy and land management, it is proposed to identify five subsets of research areas (specializations): geodesy and cartography; geoinformatics and aerospace research of the Earth; land cadastre; land management; land management. For each of the subsets of the subject area of research, a detailed description of the subject orientation is proposed, which allows to specify the context and content of the relevant research.Key words: geodesy, land surveying, subject area, field of research, doctor of philosophy, master, bachelor.